Effectiveness of Integrated Agriculture, Health Livelihood and Nutrition Interventions to Improve Maternal and Child Nutrition and Health in Rural Uganda: A Birth Cohort Study. - Kinyata, Florence; Bashaasha, Bernard, 1960- (Tufts University. Tisch Library., 2017)
This district presentation provides a summary of the data collected during the Uganda Birth Cohort Study specific to Atyak District.; Keywords: District presentation, Uganda, Birth cohort, stunting, nutrition, water, sanitation, hygeine, aflatoxin, Atyak, Makerere University.; NIL Presentations, 2016.; Accession Number: ATYAK SUBCOUNTY.pdf